Analisis Dampak Pandemi Covid-19 Terhadap Kinerja Keuangan Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2019-2020 - Restifa Ningtias; Jaeni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
The first Covid-19 virus in Indonesia occurred in March 2020. With the virus, it had an impact on the company's financial performance. This study aims to determine whether there are significant differences in the financial performance of transportation companies listed on the Indonesia Stock Exchange before and during the COVID-19 pandemic. The data used in this study is secondary data obtained from the Indonesia Stock Exchange in the form of 2019 and 2020 annual reports. 2019 financial statements for conditions before the COVID-19 pandemic and 2020 annual reports for conditions during the COVID-19 pandemic. The research variables used are Return On Equity (ROE), Quick Ratio (QR), Debt To Equity Ratio (DER), and Total Assets Turn Over (TATO). The results showed that there were significant differences in Return On Equity (ROE) and Total Assets Turn Over (TATO). Meanwhile, for Quick Ratio (QR) and Debt To Equity Ratio (DER) there is no significant difference. Keywords : Kinerja Keuangan, Return On Equity, Quick Ratio, Debt To Equity Ratio, Total Assets Turn Over